Analyzing trade-offs for sustainability requirements: A decision-making process - Dewi Saputri, Theresia Ratih; Lee, Seok Won (CEUR Workshop Proceedings, 2019)
Software engineers have a responsibility to add sustainability as a consideration while developing a software system because of the critical role of software-intensive systems in society. When sustainability composed of strongly dependent sustainable development dimensions is considered, a possibility to have conflicting requirements cannot be avoided. A decision-making process for solving the conflict with sustainability consideration should have the capability to address multiple requirements and objectives. Unfortunately, there is an inadequate study on sustainability trade-offs assessment. One of the challenges in sustainability engineering is the abstractness and complexity nature of sustainability. The lack of a comprehensive understanding of the impact of each decision in the sustainability dimension results in an unreliable outcome. By utilizing the Analytical Hierarchy Process, we propose a multi-criteria sustainability trade-offs analysis for the decision-making process. We aim to analyze the trade-offs between conflicting sustainability requirements based on the domain knowledge represented as quantified importance of stakeholders and domain-specific sustainability criteria. This approach helps to decide which alternative can remove the conflicts and minimize negatives impacts in the sustainability dimension.
Keywords: Analytical Hierarchy Process; Decision making process; Domain knowledge; Role of software; Software systems; Sustainability considerations; Sustainability criteria; Sustainability dimensions